Functional Characterization of Arabidopsis PHL4 in Plant Response to Phosphate Starvation - Wang, Zhen; Zheng, Zai; Song, Li; Liu, Dong (Frontiers in Plant Science, 2018)
Plants have evolved an array of adaptive responses to cope with phosphate (Pi) starvation. These responses are mainly controlled at the transcriptional level. In Arabidopsis, PHR1, a member of the MYB-CC transcription factor family, is a key component of the central regulatory system controlling plant transcriptional responses to Pi starvation. Its homologs in the MYB-CC family, PHL1 (PHR1-LIKE 1), PHL2, and perhaps also PHL3, act redundantly with PHR1 to regulate plant Pi starvation responses. The functions of PHR1’s closest homolog in this family, PHL4, however, have not been characterized due to the lack of its null mutant. In this work, we generated two phl4 null mutants using the CRISPR/Cas9 technique and investigated the functions of PHL4 in plant responses to Pi starvation. The results indicated that the major developmental, physiological, and molecular responses of the phl4 mutants to Pi starvation did not significantly differ from those of the wild type. By comparing the phenotypes of the phr1 single mutant and phr1phl1 and phr1phl4 double mutants, we found that PHL4 also acts redundantly with PHR1 to regulate plant Pi responses, but that its effects are weaker than those of PHL1. We also found that the overexpression of PHL4 suppresses plant development under both Pi-sufficient and -deficient conditions. Taken together, the results indicate that PHL4 has only a minor role in the regulation of plant responses to Pi starvation and is a negative regulator of plant development.